The viability of using the stormwater ponds on the Diep River in the Constantia Valley for stormwater harvesting - Rohrer, Alastair, R (Urban Water Management, 2017)
Harvesting stormwater to supplement water demands has attracted a growing interest in South Africa as concerns over the security of the country's water supply increase. Whilst stormwater harvesting has been shown to offer a viable alternative water resource, there are often concerns about its storage requirements due to space constraints in urban areas. Stormwater ponds offer a potential solution to these concerns. Since stormwater ponds are typically designed for the sole responsibility of attenuating the periodic peak stormwater flows that are associated with large storm events, they often remain underutilised. By introducing Real Time Control (RTC) systems to operate stormwater pond outlets, ponds could potentially be used to store stormwater. This could increase the benefits that stormwater ponds provide as well as offer a viable alternative water resource. To investigate the economic viability of harvesting stormwater from existing stormwater ponds, a case study was performed on a representative urban catchment – the Diep River subcatchment, located in Cape Town, South Africa. The catchment contains seven stormwater ponds, which could be retrofitted for harvesting purposes. Sixteen different stormwater harvesting scenarios were developed that modelled various non-potable demands in the vicinity as well as different storage and harvesting arrangements, created using RTC strategies, of the catchment's existing ponds. These scenarios were modelled using an assortment of modelling tools which include: a catchment stormwater model; water distribution network models; and a Life Cycle Cost Analysis (LCCA). The economic viability of harvesting stormwater from the Diep River subcatchment's stormwater ponds was most susceptible to the cost of the system's water distribution infrastructure. Consequently, stormwater harvesting was most economically viable if used to supply toilet, clothes washing and irrigation demands to residential properties situated in close vicinity to the system's harvesting pond as this minimised the extent of the water distribution network. The results also revealed that distributing storage amongst ponds situated throughout the catchment is an effective method of increasing the volume of stormwater a stormwater harvesting system could yield without reducing its economic viability. However, this is on the condition that the system only extracts stormwater from the most downstream pond in the catchment. Importantly, the study also revealed that the attenuation of peak flows of large storm events (up to 1-in-20 year return period), achieved when harvesting stormwater from the existing stormwater ponds would be comparable to what the ponds currently provide. The study concluded that harvesting stormwater from existing stormwater ponds is potentially viable. It also demonstrated an effective method to maximise a catchment's storage capacity using distributed storage. For stormwater harvesting to be viable however, stormwater should be used to supplement a large percentage of non-potable end-uses and requires significant uptake amongst catchment residents.